Smart carpark management and animation - Lee, Melvin Yu Jie (Nanyang Technological University, 2022)
Smart carpark system such as the automated carpark system helps to alleviate parking shortage problem in many urban societies. Such facilities typically require less space and can provide a huge amount of parking facilities for the citizens. With many users complained about the long waiting time and the hardware speed constraints, various manufactures are constantly finding solution to improve such constraints.